Synthesis Of Metal Oxide Coupled TiO2 Photocatalyst Particles For Enhanced Photodegradation Of Rhodamine B Dye - Tan, Zhuang Min (Universiti Sains Malaysia, 2022)
Environmental pollution is a global problem and dye pollution is one of the major factor. TiO2 shows some promising photocatalytic properties that can degrade organic pollutant under UV irradiation. However, TiO2 possesses some disadvantages such as wide band gap and high recombination rate of electron hole pairs. Coupling TiO2 with various metal oxides can enhance the photocatalytic properties. This project has used photodepositon (reduction of metal ions on TiO2) followed by thermal oxidation method for the coupling of TiO2 with CuO, ZnO and SnO2 under various methanol concentrations (25 vol% or 50 vol%) and deposition duration (1h or 3 h) to observe the effect of these parameters on the photocatalytic degradation activity on rhodamine B dye (up to 90 mins). The rate constant of photodegradation reaction (k) has improved from 0.0141 min-1 (uncoupled TiO2) to 0.0151~0.0368 min-1. Overall, CuO/TiO2 and SnO2/TiO2 samples have shown similar photocatalytic properties (average rate constants of 0.0341 min-1and 0.0327 min-1 respectively), and both performed better than ZnO/TiO2 in terms of RhB photodegradation (average rate constants of 0.0197 min-1). The difference in photocatalytic performance can be explained by the bandgap of metal oxides and their relative band positions with TiO2. Lastly, among CuO/TiO2 and SnO2/TiO2 samples, CuO/TiO2 (50,3) and SnO2/TiO2 (50,3) have shown the best photocatalytic properties respectively due to the longer deposition time and higher concentration methanol, resulting in more deposited materials.